Pengaruh Pembelajaran Praktik pada Mata Pelajaran Produk Kreatif dan Kewirausahaan Terhadap Minat Berwirausaha Siswa Kelas XII Perhotelan di SMK Negeri 3 Solok - Putri, Melliyati; Putri, Desi Armi Eka; Ikhwan, Ikhwan (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the influence of practical learning on creative product subjects and entrepreneurial interest in class XII hospitality students at SMK Negeri 3 Solok.This type of research is quantitative research. The population in the study was all class XII students at SMK Negeri 3 Solok who were registered in the 2024/2025 academic year, namely 64 people with total sampling technique. Data was collected through observation and distributed questionnaires. The analysis technique used is a simple linear regression analysis technique. The results of the research show that: practical learning with a significance level of 0.05, the magnitude of the influence of practical learning on interest in entrepreneurship is 27.1% and the tcount value is 4.804 while the ttable is 1.998, so the hypothesis is accepted. Based on the conclusion in this research, there is a positive and significant influence between practical learning on students' interest in entrepreneurship. Suggestions for students at SMK Negeri 3 Solok to be more active and enthusiastic during practical learning because it can improve skills and knowledge